Penerapan Model Kooperatif Tipe Group Investigation Pada Pembelajaran Logaritma dalam Upaya Peningkatan Aktivitas dan Prestasi Belajar Siswa - Setiawan Budi Sartati; Sripatmi Sripatmi; Nurul Hikmah (Jurnal Edukasi Sumba (JES), 2019)
Abstract: The learning of mathematics which was carried out in SMA was still concentrated on the teacher and made the students as the object of learning so that cause the low activity and the achievement of beal student of class X SMA Muhammadiyah Mataram especially on Logarithma material. To overcome this, teachers should be able to create learning that involves students actively so that student achievement could increase. One of them was by applying cooperative learning model of Group Investigation type. Therefore, a classroom action research is conducted to increase the activity and learning achievement of students of 10th of SMA (senior high school) Muhammadiyah Mataram academic year 2012/2013 on logarithmic material by applying cooperative type model of investigation group. This study was conducted in two cycles with each cycle consisting of three meetings. The success indicator of this research is the increasing of student activity activity at least active categorized and experiencing the increase of the average score from cycle to cycle two and student achievement increase if classical completeness of each cycle is classically at least 85% and reaches the average value of at least 70. Result research showed the student's learning achievement increases but has not yet reached a classical mastery. Thus, it could be concluded that the application of cooperative type study group investigation could increase the activity but not yet able to improve student achievement in the material of logarithm of 10thclass of senior high school at academic year 2012/2013.